Energy and cost analysis of an Air Cycle used as prime mover of a Thermal Electricity Storage. (June 2018) - Benato, Alberto; Stoppato, Anna
Highlights: A new Integrated Energy Storage System is presented. An Air Bottoming Cycle is used as prime mover of the Thermal Electricity Storage Unit. The plant mathematical model is implemented and tested. An energy and a cost analysis is carried out. Abstract: The increment of greenhouse gas emissions from human activities have forced the world authorities to ratify stringent environmental protection measurements devoted to the reduction of primary energy consumption and to the spread of Renewable Energy Sources (RES). To reach the fixed targets, governments have established subsidies especially to support the electricity generation from RES like wind and solar. However, the large penetration of variable and intermittent RES is stressing the need of large-scale energy storage able to stabilize the electric grids. But, available large-scale energy storage technologies like Pumped Hydro, Compressed Air Energy Storage or Flow Batteries, suffer of geographical constrains, require fossil fuel streams or are characterized by low cycle life. For this reason, in the present paper, a new Thermal Electricity Storage configuration based on the Air Bottoming Cycle (ABC) concept is proposed and tested. The off-peak power is firstly converted into thermal energy using an electric heater and, then, stored in a high temperature sensible heat storage. When the power demand is high, using a modified ABC the thermal energy is converted back into electricity. Using the plant mathematical model, an energy and a cost analyses are carried out to estimate the performance and the system feasibility.